Molecular Epidemiology of β-lactamase Production in Penicillin-susceptible Staphylococcus aureus under High-susceptibility Conditions. (4th October 2017) - Matono, Takashi; Nagashima, Maki; Mezaki, Kazuhisa; Motohashi, Ayano; Kutsuna, Satoshi; Hayakawa, Kayoko; Kaku, Mitsuo; Ohmagari, Norio
Abstract: Background: At the National Center for Global Health and Medicine (NCGM; Tokyo, Japan), prevalence of penicillin-susceptible Staphylococcus aureus isolates with penicillin G minimum inhibitory concentration (MIC) ≤ 0.12 μg/mL comprised 31% of isolates (733/2387) collected between 2013 and 2015; this is higher than those reported in previous studies. However, little is known about the prevalence of β-lactamase production in penicillin-susceptible S. aureus isolates under high-susceptibility conditions. Methods: We analyzed S. aureus isolates with penicillin G MIC ≤ 0.12 μg/mL that were recovered from in-/outpatients between 2016 and 2017. β-Lactamase production was detected by nitrocefin-based and Clinical and Laboratory Standards Institute penicillin zone-edge testing (using 10-U penicillin disc) and blaZ  PCR. Results: A total of 108 isolates were analyzed, predominantly originating from the lower respiratory tract (56%), abscesses (9%), upper respiratory tract (8%), and wounds (6%). Community- and hospital-isolated strains represented 55% and 45% of total isolates, respectively. Colonized isolates (78%) were more frequent than infected isolates (21%). All isolates were categorized as having penicillin G MIC ≤ 0.03 μg/mL using an automated system; MICs determined based on the microdilution method were 0.016 μg/mL (2%), 0.03 μg/mL (44%), and 0.06 μg/mL (54%) (Table). Notably, no isolates harbored the blaZ gene. The results from the nitrocefin-based and zone-edge tests were consistent with those obtained by PCR. Conclusion: S. aureus isolates with penicillin G MIC ≤ 0.03 μg/mL exhibited a low frequency of β-lactamase production. Thus, screening for β-lactamase production may be unnecessary for isolates showing such high-susceptibility. Disclosures: All authors: No reported disclosures.